Analiza przyczyn i konsekwencji upadków u chorych z zespołem Parkinsona = Analysis of the causes and consequences of falls in patients with Parkinson’s syndrome - Strojek, Katarzyna; Witkowska, Agnieszka; Radzimińska, Agnieszka; Kaźmierczak, Urszula; Piekorz, Zuzanna; Bułatowicz, Irena; Goch, Aleksander; Zukow, Walery (Journal of Education, Health and Sport, 2015)
Strojek Katarzyna, Witkowska Agnieszka, Radzimińska Agnieszka, Kaźmierczak Urszula, Piekorz Zuzanna, Bułatowicz Irena, Goch Aleksander, Zukow Walery. Analiza przyczyn i konsekwencji upadków u chorych z zespołem Parkinsona = Analysis of the causes and consequences of falls in patients with Parkinson’s syndrome. Journal of Education, Health and Sport. 2015;5(5):548-555. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.38788 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%285%29%3A548-555 http://pbn.nauka.gov.pl/works/685831 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 10.04.2015. Revised 15.05.2015. Accepted: 31.05.2015. Analiza przyczyn i konsekwencji upadków u chorych z zespołem Parkinsona Analysis of the causes and consequences of falls in patients with Parkinson’s syndrome Katarzyna Strojek1, Agnieszka Witkowska1, Agnieszka Radzimińska1, Urszula Kaźmierczak1, Zuzanna Piekorz1, Irena Bułatowicz1, Aleksander Goch1,Walery Zukow2 1. Uniwersytet Mikołaja Kopernika w Toruniu Collegium Medicum w Bydgoszczy, Katedra Fizjoterapii, Bydgoszcz, Polska 2. Uniwersytet Kazimierza Wielkiego w Bydgoszczy, Bydgoszcz, Polska Adres do korespondencji: dr n. med. Katarzyna Strojek Uniwersytet Mikołaja Kopernika w Toruniu Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy Katedra Fizjoterapii ul. Marii Skłodowskiej-Curie 9, 85-094 Bydgoszcz e-mail: katarzyna.strojek@gmail.com Streszczenie Choroba Parkinsona jest jednym z najczęściej występujących schorzeń ośrodkowego układu nerwowego. Oprócz najbardziej charakterystycznych objawów choroby Parkinsona, należy zwrócić uwagę na towarzyszący im ogromny problem, jakim są upadki. W przypadku pacjentów cierpiących na chorobę Parkinsona nabierają one szczególnego znaczenia, ponieważ choroba zwiększa ryzyko upadków aż 10-krotnie. Celem pracy była analiza przyczyn i konsekwencji upadków u pacjentów z chorobą Parkinsona, należących do Stowarzyszenia Osób Niepełnosprawnych „Akson” w Bydgoszczy. W wyniku przeprowadzonych badań stwierdzono, że główną przyczyną upadków u pacjentów z chorobą Parkinsona są czynniki środowiskowe. Natomiast najczęstszymi konsekwencjami upadków w badanej grupie są: uszkodzenie powłok skórnych, złamanie kości w obrębie nadgarstka, przedramienia, szyjki kości udowej. Na ryzyko upadków wpływa czas trwania choroby Parkinsona oraz wiek chorego. Abstract Parkinson’s disease is one of the most common diseases of the central nervous system. In addition to most characteristic symptoms of Parkinson’s disease, you should pay attention to the accompanying huge problem, which they are falling. In patients suffering from Parkinson’s disease and also important, because the disease increases the risk of falls to 10-fold. The aim of the study was to analyze the causes and consequences of falls in patients with Parkinson’s disease, belonging to the Association of People with Disabilities "Axon" in Bydgoszcz. The results showed that the main cause of falls in patients with Parkinson’s disease are environmental factors. In contrast, the most common consequences of falls in the study group are: skin lacerations, fractures within the wrist, forearm, hip fractures. At the risk of falls affected by Parkinson’s disease duration and age of the patient. Słowa kluczowe: upadek; zespół Parkinsona. Keywords: fall; Parkinson syndrome.